Tracing the signature dynamics of language teacher immunity - Hiver, Philip V. (2016)
The aim of this thesis is to explore the psychological qualities that set apart L2 teachers who are motivated and committed to the profession, innovative and productive in their practice, and emotionally well-adjusted from those who struggle to survive. To do this I carried out a sequence of four research phases, each building on the design and findings of previous phases. The first of these was a data-driven case study designed to investigate whether teachers who are engaged and motivated, well-adjusted and productive might provide insight into surviving as a teacher. Taking the language teacher as the complex system in which self-organized change occurs, the qualitative interview data suggested that these teachers (N = 4) had developed an emergent outcome in response to the accrued disturbances they encountered in their classroom experience. This emergent outcome—which I termed language teacher immunity—appeared to function as a defense mechanism against the material and emotional demands placed on L2 practitioners. To validate these findings, I adopted a retrodictive qualitative modeling research template for the remaining phases. The second phase used focus-group interview data from L2 professionals (N = 44) to investigate prototypes of language teacher immunity and the salient characteristics (i.e., system components) of each. These initial prototypes fit one of four global categories (i.e., productively immunized, maladaptively immunized, partially immunized, and immunocompromised). Additionally, seven components were found to be essential to the make-up of these outcomes: teaching self-efficacy; attitudes to teaching; coping; classroom affectivity; burnout; resilience; and, openness to change. Phase three triangulated the focus group phase with questionnaire data from a larger sample of L2 practitioners (N = 293). Cluster analysis of this data illustrated a core of six language teacher immunity archetypes distributed across the spectrum of global outcomes. Particular combinations of the seven components at varying levels were exhibited as specific profiles of language teacher immunity. The final phase used in-depth interview data collected from three teachers in each archetype to explore trajectories of development for each outcome, and investigate the manner in which the various archetypes manifested themselves in L2 teachers‘ sense of professional identity and motivated behavior. The data provided substantiating evidence for mapping these dynamic trajectories using a developmental blueprint (i.e., with triggering, linking, realignment, and stabilization stages) which captured the emerging pattern in these teachers‘ individual experiences and their pathways of growth. The combined evidence from this research indicates that language teacher immunity plays a significant role in L2 teachers‘ professional identity and affects how L2 practitioners position themselves in the profession through their accompanying mindsets. Furthermore, language teacher immunity outcomes are displayed in the real-time classroom choices of L2 practitioners, suggesting that language teachers‘ emotions, teaching motivation, and instructional effectiveness may hinge on the outcome of language teacher immunity that is developed.